PERTANGGUNGJAWABAN PT. KERETA API INDONESIA (PERSERO) SEBAGAI PENYELENGGARA SARANA PERKERETAAPIAN TERHADAP KECELAKAAN KERETA API (STUDI KASUS) - , Johny Pangaribuan ([Yogyakarta] : Universitas Gadjah Mada, 2012)
As one of the modes of land transportation, the train has a number of advantages, among others, in terms of its ability to carry passengers and goods massively, energy saving, efficient in using the space, has a high safety factor and low levels of contamination. Besides, the train becomes one of the alternative modes of transportation dominantly used by the society in fulfilling the needs for mobility. The objectives of this research are to identify the responsibility of PT. Kereta Api Indonesia (Persero) as the operator of the railway infrastructure toward the train accidents. The first issue analyzed is the responsibility of PT. Kereta Api Indonesia (Persero) as the operator of railway to the service users in the event of death or injury of passengers. The second issue is discussed the legal efforts undertaken by service users of the Empu Jaya Train and Gaya Baru Malam Train in defending the rights of service users. This is a normative judicial research which examine legal principles and legal systematics by examining documents as a secondary data. The field research is also conducted to obtain primary data directly from the research subject. The research result shows that the responsibility of PT Kereta Api Indonesia (Persero) toward the train accidents in Indonesia refers to the provisions of Article 28 and Article 31 of Law Number 13 Year 1992 on Railway. It is affirmed in Article 28 paragraph (1) that the Board of the organizers responsible for any losses suffered by the service user and/or third parties arising from rail freight service providers. Paragraph 2 confirms that the responsibilities referred to in paragraph (1), provided the following conditions: a. source of loss comes from the transportation service and the officer must be proven negligence, or other person employed by the organizers. b. amount of indemnity is limited with the maximum number of insurance covered by the organizers in organizing activities. Furthermore, Article 31 states that the responsibilities referred to in article 28, started since the passengers brought and/or receipt of goods and ends at the destination agreed. Furthermore, the legal efforts undertaken by the service users in defending their rights as plaintiffs include the process in the District Court of Central Jakarta, Jakarta High Court and Supreme Court.